Unsteady velocities of energetic tidal currents : an investigation into dynamic flow effects on lifting surfaces at field and experimental scale - Harding, Samuel Frederick (The University of Edinburgh, 2013)
The generation of electricity from tidal currents is an emerging industry with the potential to contribute to the UK energy supply in a predictable and sustainable way. The development of the technology requires the cost effective subsea installation of energy conversion systems in an energetic and challenging marine environment. One concept developed for the fastening of tidal energy converters to the seabed is the Active Gravity Base (AGB), which offers potential reductions in installation cost and time, relative to existing fastening methods. The performance of this concept in response to unsteady flow conditions is explored within this thesis. The dynamic behaviour of a tidal current is driven by a range of factors from gravitational forces of celestial bodies to high-frequency fluctuations of turbulent eddies. The response of the AGB concept to the unsteadiness of tidal currents is herein considered under the two broad time-scales; the directionality of the mean semi-diurnal cycle and the high frequency variations from a given mean flow velocity. The correlation between the direction and velocity of the tidal flow was assessed using hourly averaged data provided by the Admiralty Charts in the northern UK waters. The resulting directionality model was used to predict the performance of the AGB under a range of quasi-steady flow conditions. High frequency velocity measurements of a potential tidal energy site were obtained through collaboration with the University of Washington and the Pacific Northwest National Laboratory. This data was used to estimate the maximum perturbation from the mean velocity that can be expected on an annual basis. An experimental facility was developed within the re-circulating water flume at the University of Edinburgh to examine the dynamic loads generated by controllable two-dimensional flow perturbations. This was successfully achieved using a configuration of twin pitching foils with independent motion control. A relationship between the foil pitch angle and velocity perturbation time series was predicted using a vortex model of the foil wakes. This configuration was shown to be able to generate significant flow fluctuations within the range of reduced frequencies 0:06 ≤ k ≤ 1:9, with a peak gust intensity of Ig = 0:5. The numerical solution was validated against experimental results.
Keywords: unsteady tidal velocity; dynamic lift; turbulence